2018
DOI: 10.1002/cssc.201801109
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry in Higher Education: State of the Art, Challenges, and Future Trends

Abstract: Nowadays, there is increasing interest in global sustainability, and thus, university students would like to know how human actions affect the health status of our planet. This is mainly due to their basic knowledge of problems such as global warming and greenhouse gases. Students would like to gain knowledge on how to safeguard the earth for future generations. This must involve changes in education programs at interested institutions and universities. To ensure that future generations of chemists are equippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Computer-based learning is an excellent method to introduce undergraduate and graduate students with biological and biotechnological background to bioinformatics. We have shown that using bioinformatics tools as steps of a research project is more useful than presenting the same tools separately in stand-alone tutorials and that having a clear experimental objective, possibly related to a “trendy” topic such as green economy [ 38 ] raises the students’ interest.…”
Section: Discussionmentioning
confidence: 99%
“…Computer-based learning is an excellent method to introduce undergraduate and graduate students with biological and biotechnological background to bioinformatics. We have shown that using bioinformatics tools as steps of a research project is more useful than presenting the same tools separately in stand-alone tutorials and that having a clear experimental objective, possibly related to a “trendy” topic such as green economy [ 38 ] raises the students’ interest.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the application of NEMI and AES have started to appear recently, such as the evaluation of the greenness of a UPLC method for the determination of caffeine and theobromine in commercial teas [161]. In addition, an interesting review concerning the future perspectives of introducing the concepts of green chemistry at the higher education degree has been recently published [162].…”
Section: Assessment Of Methods Greennessmentioning
confidence: 99%
“…Reactions were monitored by GC in a Varian CP-3800 apparatus. 1 H NMR and 13 C NMR spectra were recorded at 400 MHz and 100 MHz, respectively on a Bruker Avance HD apparatus in DMSO-d 6…”
Section: General Remarksmentioning
confidence: 99%
“…Along this line, eliminating or reducing of the organic pollutants and development of new sustainable catalysts are two important aims of green chemistry objectives [1,2]. Nitroaromatic compounds which are potent toxic, carcinogenic and hazardous to human health are among the largest and most important groups of industrial wastes.…”
Section: Introductionmentioning
confidence: 99%